Obraz „Dafnis i Chloe” Parisa Bordona. Mitologia i erotyka - Stecyk, Monika (Sztuka i Kultura, 2015)
The paper discusses a Daphnis and Chloe painting from the collection of John Paul II Museum in Warsaw, attributed to the Venetian artist Paris Bordon. Starting with identification of the literary source – an ancient novel by Longus, recounting a love story of young shepherd Daphnis and his fiancée, Chloe – the author strives to determine the degree of its congruity with the depicted scene by conducting a detailed iconographic analysis of the latter. Furthermore, a comparative effort is made to place the picture in its supposed creator’s artistic oeuvre with regard both to its form and contents.